Tectonic evolution of the western Ordos Basin during the Palaeozoic-Mesozoic time as constrained by detrital zircon ages. Issue 4 (4th March 2019) - Zhang, Beihang; Zhang, Jin; Zhao, Heng; Nie, Fengjun; Wang, Yannan; Zhang, Yiping
ABSTRACT: The Ordos Basin has experienced a complicated tectonic evolution since the Palaeozoic. Its multi-stage evolution was closely related to the tectonic events that occurred along plate boundaries. The detrital zircon ages and crystallization age (CA)-deposition age (DA)/cumulative proportion curves obtained from Palaeozoic-Mesozoic strata from different tectonic units in and around the western Ordos Basin demonstrate that during the early Palaeozoic, the so-called Helan Aulacogen did not develop along the western Ordos Basin, the Alxa Block was an independent unit from the North China Craton, and the southern Ordos Basin was a foreland basin of the North Qinling Orogenic Belt. During the early Palaeozoic, the western Ordos Basin and its vicinity belonged to three different tectonic units (i.e. the North China Craton, the Alxa Block, and the North Qilian Orogenic Belt). At the end of the early Palaeozoic, the Alxa Block amalgamated with the Ordos Basin. From the Silurian to the Middle Devonian, the southern Alxa Block was a foreland basin of the North Qilian Orogenic Belt and underwent regional extension during the Late Devonian. During the late Palaeozoic, the western Ordos Basin and its vicinities were located in a back-arc extensional setting of the western Qinling Orogenic Belt. The southern part of the western Ordos Basin may have been a retro-arc foreland basin of the western Qinling Orogenic Belt during the Late Triassic, and the northern part of the western Ordos Basin experienced large-scale left-lateral strike-slip at the same time. The CA-DA/cumulative proportion curves can adequately explain the evolution of the western Ordos Basin during the Palaeozoic; however, the settings indicated by the CA-DA/cumulative proportion curves in intraplate evolutions are different from those proposed in other studies, which may be due to the number and distribution of samples and rapid lateral changes in sedimentary facies.